THE ROLE OF MODERN INFORMATION TECHNOLOGIES IN TEACHING BIOLOGY - Xoljurayeva Gulzoda; Akhrorova Feruza (International Scientific and Current Research Conferences, 2024)
This article explores the transformative role of modern information technologies in teaching biology. It highlights the integration of multimedia resources, virtual laboratories, and collaborative tools, which enhance student engagement and understanding of complex biological concepts. The findings indicate significant improvements in academic performance and confidence among students using technology-enhanced learning. Challenges, such as the digital divide and the need for ongoing educator training, are also discussed. Overall, the study underscores the importance of adopting innovative technologies to create inclusive and effective biology education, preparing students for future scientific endeavors and the demands of a technologically advanced society.